Fishing gear observations - Carlos, Marcelino V. (College of Fisheries, University of the Philippines, 1953)
My period of apprenticeship started on April 15, 1953. The whole period was spent on the fishing boat Marcel III owned and operated by Mariano Roldan, Navotas, Rizal. This boat is a trawler type boat of 80 feet long. During my apprenticeship I took up all phases of other trawl fishing. This includes the operation, the repair and preserving of nets and other fishing paraphernalia and marketing of catch. During interval of each trip I observed the different subsistence fishing in our locality and the nearby towns. This report therefore deals with the description of different fishing gear observation in our locality and nearby towns.